The effects of perceived organizational support in the organizational commitment behaviour of MISC employees / Haslinda Mohamad Suib - Mohamad Suib, Haslinda (2007)
The study is to identify the level of correlated Perceived Organizational Support which might have significant consequence on the Organizational Commitment Behaviour of MISC employees. The result of the study reveals that there is moderate association between the Perceived Organizational Support variables in influencing the organizational Commitment Behaviour of MISC employees. The analysis also discloses there is another variable in influencing the Organizational Commitment Behaviour of MISC employees such as age and education background.